An investigation into the effective factors on the acceptance and use of integrated health system in the primary health-care centers - Maryam Jahanbakhsh; Hamid Reza Peikari; Farzaneh Hazhir; Sakineh Saghaeiannejad-Isfahani (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: The successful application of the information systems in the health-care domain requires a reasonable recognition of the factors affecting the acceptance and use of such systems. The study aimed to investigate the factors affecting the acceptance and use of an integrated health system (IHS) in Isfahan primary health centers. MATERIALS AND METHODS: It was an applied and descriptive-analytical survey conducted in Isfahan, Iran. Research population included all IHS's users in the health centers no. 1 and 2 of Isfahan city from which a sample of 320 individuals were selected in total. Data were collected using a questionnaire developed based on the Unified Theory of Acceptance and Use of Technology model. Data were analyzed using partial least squares (PLS) method and SmartPLS software. RESULTS: The users' behavioral intention to use the IHS system was influenced by performance expectancy, effort expectancy, and social influence, but it was not significantly related to facilitating conditions. Behavioral intention to use the IHS also had a significant relationship with the use of system. Furthermore, performance expectancy was the most important predictor. CONCLUSIONS: According to the findings, if the system users perceive the positive role of system in performance improvement, its convenience to use, and positive attitude of others toward it, their willingness to accept and use system will increase. Furthermore, it was important for the users that the system helps them in resolving their daily work-related problems and making rational decisions.